The Importance of Using 4K Model Skills In The Acmeological Development Of Future Educators In The Design Of Modern Training - Dоniyоrоva Dildora Nuritdin qizi (Innovative Technologica: Methodical Research Journal, 2026)
This article highlights the role and importance of the 4K model (creativity, critical thinking, collaboration and communication) in the process of acmeological development that guides future preschool teachers to the peak of professional maturity. In the course of the study, the psychological and pedagogical possibilities of 4K skills in the formation of motivation for self-development and professional success in students were analyzed. Each component of the 4K model is justified by the author as a motivational factor that strengthens the acmeological position of the future specialist. At the end of the article, methodological recommendations aimed at ensuring the personal and professional growth of students in the process of higher education are put forward